Psychometric properties of a Spanish version of the 10-item Berger's stigma scale in Colombia: a validation study: Propiedades psicométricas de una versión en español de la escala de Berger de diez ítems en Colombia: un estudio de validación - Montaño, David; Martínez-Cajas, Jorge; Balfour, Louise; Mueses, Héctor Fabio; Galindo, Jaime; Alvarado, Beatriz (ARS MEDICA Revista de Ciencias Médicas, 2020)
Introduction: HIV-related stigma is detrimental to people living with HIV (PLH), and reducing it is essential for achieving an HIV/AIDS-free generation. Abbreviated stigma scales can improve the feasibility of surveys that broadly explore factors affecting PLH. This study tested the psychometric properties of a Spanish translation of the abbreviated 10-item Berger's HIV stigma scale. Methods: We recruited a sample of 105 PLH regularly attending a specialized clinic in Cali, Colombia. English-to-Spanish and Spanish-to-English back translation was performed of the Berger's 10-item HIV stigma scale. Exploratory and confirmatory factor analyses were carried out to assess its validity. Pre- and post-test reliability (15 days) was estimated with the intra-class correlation coefficient (ICC). Results: The Confirmatory Factor Analysis (CFA) was used to confirm a two-factor solution with three poor items removed, resulting in a 7-item HIV Stigma Scale. The resulting 7-item HIV stigma scale had a Cronbach's alpha of 0.73 with an ICC of 0.83 (CI 95%: 0.75–0.89). One factor loaded three items related to negative self-image (internalised stigma), and the other four items were related to personalized (enacted) HIV stigma. Both factors were related to depression and adherence to antiretroviral therapy. Conclusion: The Spanish translation of the 10-item HIV stigma scale did not perform well due to problems in items 4, 5, and 6. Rather, a modified 7-item version had a good fit with a two-factor loading in which both HIV stigma factors correlated significantly with depression and HIV medication adherence.